Treatment of a subcutaneous tibialis anterior tendon rupture with a semitendinosus autograft - Zmerly, Hassan; Russo, Marco; Ceccoli, Matteo; Moscato, Manuela; Akkawi, Ibrahim (Acta Biomedica Atenei Parmensis, 2023)
The subcutaneous rupture of the tibialis anterior tendon is a rare and silent lesion which can lead to foot and ankle dysfunction with gait difficulty. The treatment can be either conservative or surgical. Conservative management is reserved for inactive patients and those with a general or local contraindication to surgery, whereas surgical repair includes direct and rotational suture, as well as tendon transfer and auto- or allograft. The choice of surgical treatment is based on multiple factors, including the symptoms, the timespan from injury to treatment, the anatomopathological pattern of the lesion, and the patient’s age and level of activity. Large defects present a particular reconstructive challenge, and there is no consensus on the optimal method of treatment. That being said, one of the options is an autograft using the semitendinosus hamstring tendon. We present a case of a 69-year-old woman who sustained a hyperflexion trauma to her left ankle. Three months later, ultrasound examination and a magnetic resonance imaging showed a complete tibialis anterior rupture with a gap of more than 10 cm. The patient was successfully treated with surgical repair. An autograft of the semitendinosus tendon was used to bridge the gap. The tibialis anterior rupture is a rare lesion that must be promptly diagnosed and treated, especially in physically active patients. Large defects pose particular challenges. Surgical management was found to be the treatment of choice. In the case of a lesion with a major gap, semitendinosus grafting can be successfully employed.